WOMAN STRUGGLE IN CAHAYA CINTA PESANTREN NOVEL BY IRA MADAN - Melinda Rahma Lubis and Syamsul Bahri (LINGUISTICA, 2017)
The title of this thesis is Woman Struggle in Cahaya Cinta Pesantren Novel by Ira Madan. This study aims to analyzing how is the woman struggle for her ambition of  Marshila Silalahi  in term of hierarchy of needs that she had faced. The source of the data of the analysis is Cahaya Cinta Pesantren novel and the data are the linguistic features that are formed as sentences by the first woman main character. The writer applies the theories from Maslow (1943) about the hierarchy of needs. Based on its form, Maslow was devided the struggle into 5 stage model, they are (1) Physiological needs, (2) Safety needs, (3) Love and Belonging needs, (4) Esteem needs, (5) Self-actualization. The writer devided the data based on each types of self-actualization by Maslow in Hierarchy of needs. Struggle is related to subconscious mind phychologically, the female character is potrayed to reach her ambition with personal reasons to get something in her struggle. The sources of data of this research are any statements, dialogues and actions that prove or describe the self-actualization of a woman struggle in the novel Cahaya Cinta Pesantren (2014) by Ira Madan. Finally the struggles in each types of selfactualization can be interpreted through Marshila Silalahi sentences of the novel and it is found that hierarchy of needs reflect woman struggle.